Spatial distribution and pattern of heavy metals in urban soils of Yogyakarta, Indonesia - Magno, J. L. (2022)
Heavy metals contamination is becoming a global problem in urban areas. With that, understanding spatial distribution and pattern of heavy metals in urban soils is a crucial step toward sustainable urban development. This study intends to assess the spatial distribution and pattern of four heavy metals (Pb, Cu, Zn, and Cd) in Yogyakarta City outward in the boundaries of Sleman and Bantul Regencies. In relation, we utilized geostatistical method Empirical Bayesian Kriging (EBK) then correlated to Land Cover/Use data for the spatial analysis of heavy metals concentration. The degree of contamination was quantified using indices - PI (Pollution Index), Igeo (Geo-accumulation Index), and PLI (Pollution Load Index). We show that by analysing the Pb, Cu, Zn, and Cd elements of 168 urban soils samples collected, Yogyakarta City, a densely populated area, serves as a place of heavy metals contamination hotspots. Pb and Cu is posed as moderately contaminated, whereas Zn and Cd is considered as uncontaminated (as majority of Zn and Cd values does not exceed the background values). But in overlapping consideration of four heavy metals contamination, they are classified as moderately contaminated (PLI=1.10). In summary, heavy metals contamination in soils varies as a function of urbanization. © Published under licence by IOP Publishing Ltd.